Beta-blocker treatment in atrial fibrillation with chronic obstructive pulmonary disease: a Danish nationwide study from 1995 to 2015. (14th October 2021) - Benson, C S; Dalgaard, F; Rasmussen, P V; Hansen, M L; Lamberts, M; Ruwald, M H; Pallisgaard, J; Gislason, G; Torp-Pedersen, C; Uffe Bodtger, U; Jensen, M; Rasmussen, D B
Abstract: Background: Atrial fibrillation (AF) and chronic obstructive pulmonary disease (COPD) often coexist. Beta-blockers are a mainstay of treatment in AF and are considered safe in COPD patients after myocardial infarction, though real-life studies have demonstrated significant under-use. Little is known on the utilization patterns in patients with AF and COPD. Purpose: To investigate the temporal trends of beta-blocker utilization in patients following first diagnosis of AF in a hospital setting, with and without concomitant COPD, and determine clinical factors associated with beta-blocker use. Methods: A nationwide study from 1995 to 2015 using data from the comprehensive Danish health registers. All patients with first registered AF diagnosis in a hospital setting were included. Beta-blocker use was identified by claimed prescriptions within 90 days following AF diagnosis. Factors associated with beta-blocker use or non-use in COPD patients during the most recent period (2010–2015) was examined using multivariable logistic regression and presented as odds ratios (OR) with 95% confidence intervals (95% CI). Results: A total of 264 180 patients were included, of these 31 981 (12.1%) had COPD. Patients with concurrent COPD were older than those without COPD (median age 76 vs. 74 years), the proportion of males was similar (54%) and patients with COPD had more comorbidities, particularly cardiovascular disease. Across the 21-year study period, fewer patients with COPD used beta-blockers after AF diagnosis, than those without COPD (38.8% vs. 53.2%, p<0.001). Beta-blocker use increased in both groups during the study period (Figure 1). Nevertheless, the proportion of users was consistently lower among patients with COPD, although the difference was smaller during the most contemporary year (2015: 55.5% vs. 61.6% in COPD vs. non-COPD respectively). Predictors for decreased beta-blocker use included high age, COPD severity represented by use of triple inhaled therapy (OR 0.84 [95% CI 0.77–0.92]), and a history of frequent COPD exacerbations (OR 0.80 [95% CI 0.74–0.86]) (Figure 2). In a subgroup of COPD patients with complete clinical data from the Danish Register of COPD, severe airflow limitation (Forced Expiratory Volume in 1 second <30% of predicted) and high grade of dyspnoea (Modified Medical Research Council Dyspnoea scale 3–4) were associated with decreased odds for beta-blocker use (OR 0.48 [95% CI 0.38–0.59] and OR 0.67 [95% CI 0.55–0.80], respectively). Conclusions: Beta-blocker use in patients with AF and concurrent COPD have increased considerably over a 21-year period yet remained less used than in patients without COPD. The severity of COPD was a strong negative predictor for beta-blocker use following AF diagnosis, suggesting a fear for adverse effects. The lower use of beta-blocker treatment in patients with severe COPD and AF might suggest underuse and warrants further evaluation. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Naestved - Slagelse - Ringsted Hospitals, Region Sjaelland, Denmark